2008
DOI: 10.1016/j.envres.2007.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Scalp hair and urine mercury content of children in the Northeast United States: The New England Children's Amalgam Trial

Abstract: Children may be at particular risk from toxic effects of mercury (Hg). Previous studies of hair (organic) and urine (inorganic) Hg levels in US children were unable to assess Hg levels while accounting for exposure to amalgam dental restorations. This analysis describes, over a 5-year period, levels and correlates/predictors of scalp hair (H-Hg) and urinary (U-Hg) mercury in 534 New England Children's Amalgam Trial (NECAT) participants, aged 6-10 years and without exposure to dental amalgam at baseline. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Creatinine excretion was higher for boys compared to girls (P≤0.03) (Trachtenberg and Barregard, 2007). Mercury and NAG did not vary significantly by gender (Trachtenberg and Barregard, 2007, Dunn et al, 2008). …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Creatinine excretion was higher for boys compared to girls (P≤0.03) (Trachtenberg and Barregard, 2007). Mercury and NAG did not vary significantly by gender (Trachtenberg and Barregard, 2007, Dunn et al, 2008). …”
Section: Resultsmentioning
confidence: 87%
“…The excretion of creatinine and γ-GT increased significantly with age (P<0.001) (Trachtenberg and Barregard, 2007), while mercury excretion decreased with age (P=0.01) (Dunn et al, 2008). Albumin, NAG, and A1M did not significantly change with age (Trachtenberg and Barregard, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dunn et al (2008) examined US children over a 5-year period and found that the a Exposure was measured by counting the number of restorations using amalgam then an exposure score was computed by first giving scores of 1.0, 2.0, or 3.0 for small, medium, or large restorations, respectively, then adding these scores for each restoration of each tooth. Exposure for baby teeth was taken to be one half the exposure for adult teeth (i.e., 0.5, 1.0, 1.5 for small, medium, and large restorations).…”
Section: Discussionmentioning
confidence: 99%
“…122,124,125,141,156,176,177 Dental amalgam raises the body burden of mercury, but may not to lead to clinically observable symptoms in children.…”
Section: Diagnosis Of Mercury Intoxicationmentioning
confidence: 99%